Characterization, classification and evaluation of land resources for management of Bareli watershed in Seoni district, Madhya Pradesh using Remote Sensing and GIS - INGLE, SAGAR N.; NAGARAJU, M.S. S.; SAHU, NISHA; KUMAR, NIRMAL; TIWARY, PRAMOD; SRIVASTAVA, RAJEEV; SEN, T. K.; NASRE, R. A. (Journal of Soil and Water Conservation, 2020)
The land resources of Bareli watershed in Seoni district of Madhya Pradesh were characterized, classified and evaluated using IRS-LISS-IV and LISS-III data and GIS. Five major landforms viz. plateau, escarpement, isolated mound, hills and ridges and pediment were identified and delineated. Based on image characteristics, five major land use/ land cover viz. forest, cultivated land, wasteland, habitation and water bodies were identified. Five slope classes viz., very gently sloping (1-3%), gently sloping (3- 5%), moderately sloping (5-10%), strongly sloping (10-15%) and moderately step to steep sloping ( 15- 15%) lands have been identified using Cartosat-1 DEM (30 m resolution) and topographic information. Five soil series (Diwartola, Diwara, Bareli-1, Bareli-2 and Bareli-3) were tentatively identified and mapped as mono series on 1:10000 scale based on landform-soil relationship. Soils are shallow, clayey, well drained and severely eroded at upper elevations, whereas, they are moderately deep, clayey, moderately well drained with moderate erosion at lower elevations. The soils are, in general, clayey, neutral in reaction, non-saline and non-calcareous and qualify for Lithic Haplustepts/ Lithic Ustorthents/ Vertic Haplustepts/ Typic Ustorthents at subgroup level. The soils were grouped under land capability sub classes IVs and IVst and 2st, 3s, 3st and 4st land irrigability sub-classes. The soils of Diwartola are moderately suitable for growing sorghum and marginally suitable for growing cotton, pigeonpea, maize and rice and not suitable for growing soybean. The soils of Diwara and Bareli-2 are marginally suitable for sorghum and not suitable for growing cotton, pigeonpea, soybean, maize and rice. The soils of Bareli-1 and Bareli-3 are moderately suitable for growing sorghum and marginally suitable for growing cotton, pigeonpea, soybean, maize and rice. Suitable land use interventions and soil and water conservation measures have been suggested for better management of land resources in the watershed.